Educators' open educational collaboration online: The dilemma of emotional ownership. (March 2017) - Pirkkalainen, Henri; Pawlowski, Jan M.; Pappa, Dimitra
Abstract: The open education movement has witnessed ups and downs from initial interest in transparency and openness, followed by a lack of reuse of open educational resources (OER) and the massive boost of interest in massive open online courses (MOOCs). This article addresses educators' online behaviors and perceptions regarding participation in collaborative development of OER in online settings. Using a data-driven approach to study educators' perceptions, this article presents multiple considerations for collaborative OER development and validates a new model explaining educators' intention to participate in collaborative action. The findings reveal the contradictory nature of emotional ownership of knowledge: a critical enabling factor for commitment and a barrier to knowledge exchange in an open and transparent manner. The findings also show how outcome expectations regarding increase in reputation and status in the network do not influence the intention to share knowledge. Further interviews with idea-sharing platform users enable us to explain the favorable settings to resolve the dilemma of emotional ownership. The study contributes not only to further development of the open education movement but also to theory development of educators' collaborative behaviors online. Highlights: Explained the contradictory nature of emotional ownership of knowledge. Revealed critical influencing factors to educators' online collaborative behavior. Discussed the enabling factors of collaborative OER development online.